The Dynamics of Law and Justice in the Perspective of Law Enforcement Against Illegal Mining in West Kalimantan - M. Qahar Awaka; Lomba Sultan; Abdul Wahid Haddade (CBJIS: Cross-Border Journal of Islamic Studies, 2025)
The enforcement of illegal laws from a legal and justice perspective is the main focus of this study, particularly in the context of West Kalimantan Province. The enforcement of laws that do not comply with existing legal provisions can lead to systemic injustice. This study explores the dynamics of law and justice in the context of illegal law enforcement in West Kalimantan, highlighting the role of Islamic law in the process. Using a qualitative approach, data was collected from various sources, including interviews with policymakers, legal practitioners, and local communities. The findings highlight the complex challenges faced in illegal law enforcement, including issues of legality, culture, and society. This study also considers the impact and implications of illegal law enforcement on social justice and legal stability in West Kalimantan. The findings of this study are expected to provide deeper insights into the dynamics of law and justice in the context of illegal law enforcement in the region.